The Passionate Torah : Sex and Judaism. - Ruttenberg, Danya (NYU Press, 2009)
In this unique collection of essays, some of today's smartest Jewish thinkers explore a broad range of fundamental questions in an effort to balance ancient tradition and modern sexuality. In the last few decades a number of factors--post-modernism, feminism, queer liberation, and more--have brought discussion of sexuality to the fore, and with it a whole new set of questions that challenge time-honored traditions and ways of thinking. For Jews of all backgrounds, this has often led to an unhappy standoff between tradition and sexual empowerment. Yet as The Passionate Torah illustrates, it is of.